DESIGN, MANUFACTURING, AND TESTING OF TWISTEDÃâÃâDARRIEUS WIND TURBINE AS ELECTRICAL POWER GENERATOR FOR BTS TOWER - LESTALUHU (NIM : 13105071); Pembimbing 1 : Prof. Dr. Ir. T. A. Fauzi Soelaiman Pembimbi, RAKSHIDATU
Indonesia's energy problems increase along with increasing national energy demand. These conditions made worse by the high dependence of national energy to fossil fuel while the reserves are limited from year to year. Telecomunication as one of sectors that is growing rapidly in line with indonesiaÃ‚Â’s development, become a sector that depends on fossil fuel. Nowadays, most off-grid BTS towers use fossil fuel as the main power source. In response to enviromental issue, many telecomunication companies is try to develop Base Tranceiver Station (BTS) that is more enviromental friendly. The success key of this effort is to reduce the power consumption of the system. This kind of developing effort is known as Green-BTS. Wind, as one of renewable energy resources, has a high potential as power source for BTS tower. The BTS tower structures are mostly located at high elevation, where the wind blows strong. In this research, wind energy will be developed as a power source for Green-BTS tower. This research uses twisted Darrieus wind turbine as the main power converter. The design and manufacturing phase were applied to the prototipe size. With teoritic power calculation meets to minimum electrical needs for Green-BTS tower. So, it can subtitute the main electrical power of a Green-BTS tower. For the testing phase, a 1:6 model was tested in a sub-sonic wind tunnel. The result of the test shows that the wind turbine rotor, can self start, and work properly at 8 m/s wind velocity. The maximum power coefficient was calculated on 0,125% that reached at 14 m/s wind velocity.